2005
DOI: 10.1002/jcb.20735
|View full text |Cite
|
Sign up to set email alerts
|

Role of wnts in prostate cancer bone metastases

Abstract: Prostate cancer (CaP) is unique among all cancers in that when it metastasizes to bone, it typically forms osteoblastic lesions (characterized by increased bone production). CaP cells produce many factors, including Wnts that are implicated in tumor-induced osteoblastic activity. In this prospectus, we describe our research on Wnt and the CaP bone phenotype. Wnts are cysteine-rich glycoproteins that mediate bone development in the embryo and promote bone production in the adult. Wnts have been shown to have au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
0
3

Year Published

2007
2007
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(123 citation statements)
references
References 84 publications
0
120
0
3
Order By: Relevance
“…The reason for effective treatment targeting bone resorption may be mainly because of the osteolytic initial stage during the establishment of the bone metastasis. Recent studies on Wnt signalling have shown important evidence that prostate cancer to bone metastasis might transit from an early osteolytic stage to late osteoblastic stage (Hall et al, 2005(Hall et al, , 2006(Hall et al, , 2008. We found that overexpression of Id-1 in LNCaP cells reduced their ability to stimulate osteoblast mineralisation and enhanced their ability to promote osteoclast differentiation, whereas Id-1 knockdown in PC3 cells reduced their ability to stimulate osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 63%
“…The reason for effective treatment targeting bone resorption may be mainly because of the osteolytic initial stage during the establishment of the bone metastasis. Recent studies on Wnt signalling have shown important evidence that prostate cancer to bone metastasis might transit from an early osteolytic stage to late osteoblastic stage (Hall et al, 2005(Hall et al, , 2006(Hall et al, , 2008. We found that overexpression of Id-1 in LNCaP cells reduced their ability to stimulate osteoblast mineralisation and enhanced their ability to promote osteoclast differentiation, whereas Id-1 knockdown in PC3 cells reduced their ability to stimulate osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 63%
“…The osteoinductive properties of GSK3b inhibitors have been demonstrated both in vivo and in vitro by numerous investigators (Gregory et al, 2006), proteasomal inhibitors have been shown to reduce Dkk-1 and RANKL levels (Terpos et al, 2006), and the benefits of administration of an anti-Dkk-1 antibody have recently been demonstrated in a murine model of multiple myeloma (Yaccoby et al, 2007). However, it remains to be seen whether the induction of Wnt signalling either by GSK3b inhibition, or by antibody administration may affect the metastatic potential of OS cells since Wnt signalling and/or b-catenin upregulation has been shown to be a key regulator of migration in prostate tumours, multiple myeloma cells and also in OS cells (Iwaya et al, 2003;Qiang et al, 2005;Hall et al, 2006). Although we did not detect signs of pulmonary metastasis in this study, further investigation employing highly metastatic OS cell lines should be performed in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer cells induce osteoblastic metastases through activation of Wnt signaling. 52,59 DKK1 was found to block prostate cancer-associated osteoblastic metastases without affecting tumor growth, while inhibition of DKK1 in osteolytic prostate cancer cells altered the nature of bone metastases from osteolytic to osteoblastic. 59 Consistent with this notion, DKK1 was found to increase early in prostate cancer and decrease as tumors progress from primary tumor to metastasis.…”
Section: Dkk1 In Osteolytic and Osteoblastic Metastasesmentioning
confidence: 99%